ANALISIS FRAMING DETIK.COM DALAM PEMBERITAAN ADZAN DI MEDIA PERANCIS AGENCY FRANCE PRESSE - Viky Ardinza; Galih Akbar Prabowo (Institut Agama Islam Negeri Ponorogo, 2024)
This study examines five news published by the online media Detik.com about the news of the French foreign media Agency France Presse (AFP), which highlights the call to prayer in Indonesia by uploading a news entitled